The Impact of Ribulose-5-Phosphate Isomerase Enzyme and Zinc on Leukemia - Mohammed, Maha Fadel; Shaker, Asmaa Hashim (American Journal of Bioscience and Clinical Integrity, 2025)
Leukemia is a malignancy that affects blood cells and the tissues responsible for their formation, such as bone marrow and the lymphatic system. It results from mutations in hematopoietic stem cells, leading to abnormal proliferation and accumulation of cells, which impairs normal hematopoiesis. Types of leukemia include acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), chronic myeloid leukemia (CML), and chronic lymphocytic leukemia (CLL). Common symptoms include anemia, bleeding, recurrent infections, and hepatosplenomegaly. Diagnosis is based on blood tests, bone marrow biopsy, genetic analysis, and imaging studies. Treatment options include chemotherapy (mainstay for AML, though less effective in the elderly) and stem cell transplantation, especially in younger patients. This study investigates the activity of the enzyme ribulose-5-phosphate isomerase (RPI) and evaluates the role of zinc in the metabolic and biochemical status of patients with leukemia. Understanding these factors may provide insights into the disease’s pathophysiology and potential therapeutic targets.